Amplification of active sites and porosity for the adsorption of QDs via the induction of the rare-earth element la into TiO2 for enhanced photovoltaic effects in QDSSCs. (19th November 2020) - Shwetharani, R.; Sushmitha, T.; Preethi, G. U.; Balakrishna, R. Geetha
Abstract : Schematic representing preparation of TiO2  and La–TiO2,   QDSSCs device development and mechanism of charge carrier's migration in device along with IV curve for La–TiO2 . Abstract : Quantum dot-sensitized solar cells (QDSSCs) have emerged as an attractive area of research, enabling the construction of efficient third-generation photoelectrochemical solar cells with a higher theoretical photon conversion efficiency of up to 44%. The power conversion efficiency ( η ) rates of several QDSSCs are lower than those of dye-sensitized solar cells, reaching a maximum of 13.4%; meanwhile, the major drawbacks of QDSSCs are their narrow absorption range and the recombination of charge carriers occurring at the QD- and TiO2 -electrolyte interfaces. Tailoring the band structure is an efficient pathway to facilitate charge carrier transportation, which in turn enhances light absorption and reduces charge carrier recombination. Doping/modifying the electron transport layer (ETL), namely TiO2, with rare earth elements has been proved to enhance the catalytic activity. Here, we report the investigation of incorporation of La 3+ into TiO2 to tailor its band structure and physical characteristics of ETL; this remarkably enhanced the photon conversion efficiency (PCE) of the La–TiO2 photoanode to 3.28%, with a charge transfer resistance of 452.21 Ohm, in contrast to the PCE of TiO2 (0.87%). The study indicates successful incorporation of La 3+, oxygen vacancies, efficient charge carrier separation, band gap reduction, favorable band gap alignment for effective electron transfer, a broad visible light absorption range, reduced particle size and enhanced surface area in the rare earth element-doped nanostructured titania. The obtained characteristics of the La-doped TiO2 were exploited as an ETL in QDSSCs to boost their photovoltaic performance.